Blood Culture Positivity Rate: Antibiotical Therapy Impact Before Sample Collection in Sepsis Patients - Sri Kartika Sari; Andaru Dahesihdewi; Osman Sianipar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Sepsis is one of the significant causes of global morbidity and mortality. One of the keystones of sepsis diagnosis and treatment is the Blood Culture (BC) test. BC performed after intravenous Antibiotic Administration (AA) appears to reduce the culture positivity rate. This study aimed to evaluate the influence of AA before obtaining blood culture samples on the positivity rate. This was a retrospective cohort study, conducted from January to February 2020 on patients with suspected sepsis at the Mataram General Hospital from January to December 2019. Patients with valid blood culture tests were included. Out of 178 suspected sepsis patients, 138 samples were culture-negative, and 40 samples were culture-positive. Out of 40 culture-positive patients, 23 (57.5%) samples were obtained before AA, whereas other 17 samples (42.5%) were obtained after AA. In addition, among 138 culture-negative patients, 101 (73.2%) subjects received antibiotics before sampling, and only 37 (26.8%) subjects received antibiotics after sampling. There was a significant difference in the blood culture positivity results between samples taken before and after AA (p=0.001). Samples were taken before AA had a 3.69 times greater possibility of positive culture results than samples taken after AA (OR 3.69; 95% CI 1.77-7.67; p= 0.0005). The percentage of positive culture results among subjects receiving antibiotics before sampling was highest (20%) in those whose samples were taken less than an hour before the next AA. Antibiotics administration of sepsis patients before blood culture sampling gives a lower positivity rate than AA after blood culture sampling.